A CFD Study of Industrial Double-Cyclone in HDPE Drying Process - Razavi Alavi, S.A.; Nemati Lay, E.; Alizadeh Makhmali, Z.S. (Ital Publication, 2018)
Double-cyclone in fluidized bed drying is an important equipment which reflects the conditions of drying in HDPE slurry process. Cyclone is an important unite of fluidized bed drying in order to move the solid particles outward to its wall. Therefore, flow pattern created in fluidized bed will affect industrial cyclones installed in dryer for dust removing. Pressure drop of the cyclones is an effective parameter represents the drying behavior. Substantially, geometry of cyclone, inlet flow rate of gas, density and particle size distribution (PSD) can affect the pressure drop value. Fluidized bed hydrodynamic regime is very complex and must be understood to improve fluidized bed operations through theoretical, industrial and CFD study of double-cyclone. Pressure drop is introduced as parameter related to the cyclone efficiency can be calculated with ANSYS Fluent software in the Eulerian-Lagrangian framework with RNG k-É› turbulence model used as a mathematical method. Proper pressure drop concluded from industrial experiments and CFD calculation shows good fluidization of HDPE particles in the bed of nitrogen and powderÂ to reach the best fluidized bed situation and suitable quality of HDPE powdery product.